Bridging Thermal Infrared Sensing and Physically‐Based Evapotranspiration Modeling: From Theoretical Implementation to Validation Across an Aridity Gradient in Australian Ecosystems. Issue 5 (13th May 2018) - Mallick, Kaniska; Toivonen, Erika; Trebs, Ivonne; Boegh, Eva; Cleverly, James; Eamus, Derek; Koivusalo, Harri; Drewry, Darren; Arndt, Stefan K.; Griebel, Anne; Beringer, Jason; Garcia, Monica
Abstract: Thermal infrared sensing of evapotranspiration ( E ) through surface energy balance (SEB) models is challenging due to uncertainties in determining the aerodynamic conductance ( gA ) and due to inequalities between radiometric ( TR ) and aerodynamic temperatures ( T 0 ). We evaluated a novel analytical model, the Surface Temperature Initiated Closure (STIC1.2), that physically integrates TR observations into a combined Penman‐Monteith Shuttleworth‐Wallace (PM‐SW) framework for directly estimating E, and overcoming the uncertainties associated with T 0 and gA determination. An evaluation of STIC1.2 against high temporal frequency SEB flux measurements across an aridity gradient in Australia revealed a systematic error of 10–52% in E from mesic to arid ecosystem, and low systematic error in sensible heat fluxes ( H ) (12–25%) in all ecosystems. Uncertainty in TR versus moisture availability relationship, stationarity assumption in surface emissivity, and SEB closure corrections in E were predominantly responsible for systematic E errors in arid and semi‐arid ecosystems. A discrete correlation ( r ) of the model errors with observed soil moisture variance ( r  = 0.33–0.43), evaporative index ( r  = 0.77–0.90), and climatological dryness ( r  = 0.60–0.77) explained a strong association between ecohydrological extremes and TR in determining the error structure of STIC1.2 predicted fluxes. Being independent of any leaf‐scale biophysical parameterization, the model might be an important value addition in working group (WG2) of the Australian Energy and Water Exchange (OzEWEX) research initiative which focuses on observations to evaluate and compare biophysical models of energy and water cycle components. Plain Language Summary: Evapotranspiration modeling and mapping in arid and semi‐arid ecosystems are uncertain due to empirical approximation of surface and atmospheric conductances. Here we demonstrate the performance of a fully analytical model which is independent of any leaf‐scale empirical parameterization of the conductances and can be potentially used for continental scale mapping of ecosystem water use as well as water stress using thermal remote sensing satellite data. Key Points: Thermal remote sensing of evapotranspiration is critical due to uncertainties in aerodynamic temperature and conductance estimation We integrated radiometric temperature into Penman‐Monteith Shuttleworth‐Wallace framework to directly estimate conductances and evapotranspiration Moderate to low systematic errors in evapotranspiration across an aridity gradient in Australia